2012
DOI: 10.5799/ahinjs.01.2012.02.0138
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of treatment with enoxaparin in lichen planus

Abstract: ÖZETAmaç: Heparin analoglarının düşük dozlarının antiproliferatif ve immünmodülatör etkilerinin olduğu bilinmektedir. Bu çalışmanın amacı; liken planusta düşük doz enoxaparinin etkinliğini değerlendirmektir. Gereç ve yöntem:Liken planus tanısı alan 21 hasta 12 hafta boyunca tedavi edildi. Hastalara her hafta 3 mg enoxaparin subkutan enjeksiyonla yapıldı. Etki ve güven-lik verileri kaydedildi. Bulgular:Tam iyileşme hastaların 15' inde (%71), belirgin düzelme 4' ünde (%19) tespit edildi. Hastaların 2'sinde (%9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They reported disease improvement in 26 out of 31 patients. Ucmak and co-workers reported distinctive recovery of the disease in 71% of patients (15 out of 21) treated with enoxaparin for 12 weeks ( Uçmak et al, 2012 ). Neville et al (2007) demonstrated a sustained clinical response to enoxaparin in a patient with recalcitrant ulcerative LP resistant to oral corticosteroids.…”
Section: Enoxaparinmentioning
confidence: 99%
“…They reported disease improvement in 26 out of 31 patients. Ucmak and co-workers reported distinctive recovery of the disease in 71% of patients (15 out of 21) treated with enoxaparin for 12 weeks ( Uçmak et al, 2012 ). Neville et al (2007) demonstrated a sustained clinical response to enoxaparin in a patient with recalcitrant ulcerative LP resistant to oral corticosteroids.…”
Section: Enoxaparinmentioning
confidence: 99%